Proposal to solve workload problems in the simulator of the Wolf architecture - Cavenaghi, M. A.; Martini, J. A.; Neto, A. G. (Institute of Electrical and Electronics Engineers (IEEE), 2000)
Presents an approach that has been proposed in order to investigate the workload balance problems in a simulator of the Wolf parallel architecture, known as Saw (Simulator of Architecture Wolf). This approach can be applied to the simulator in order to eliminate overloaded and underloaded units observed during the first experiments on the Wolf architecture. The unexpected results obtained are well-understood if one considers that the architecture simulated is based on a circular pipeline: if there is only one overloaded (or underloaded) unit in the simulator, it can affect the performance of the entire system, adding latency to it. The first attempt to improve the results obtained with the simulator was to calibrate all of the simulator units. The approach used leads to the necessity of dividing the units into two categories: grouped units and isolated units. These two categories are analyzed separately, resulting in modifications to the original architecture.